Montgomery's auditing - Lenhart, Norman J.; Defliese, Philip L. (New York : Ronald Press Co., 1957)
This edition set forth the principles underlying the theory and practice of auditing.
Includes index.
ucj 18/01/2019
Loans
Keywords: Montgomery, Robert Hiester; Auditing